Implementation of Deradicalization Policy For Terrorism Prisoners: An Indonesian Case - Sutrimo Sumarlan (The Republic of Indonesia Defense University, 2016)
This research examined how Indonesia experiences in implementing the policy of deradicalization for prisoners of terrorism after free from prison in order to not involved reiteration radicalism of terrorism. Researcher examined what factors are supporting and inhibiting for effectiveness of success by using Grindle’s theoretical model of implementation, and trying to offer an alternative model that fits for implementing the policy of deradicalization for prisoners of terrorism, and other cases of social violence. This research used qualitative descriptive approach, and resulted that implementing the policy of deradicalization would might be more effective success if accompanied by intense social communication factor between government and certain society such as religious organizations to build a common perception of terrorism; and monitoring and forcasting factors for ex-prisoners of terrorism which involves intensive religious figures with a socio-economic approach and fostering religious stabilization.